Systematic literature review and meta‐analysis of concordance and accuracy of pretransfusion immunohematology routine tests - Elliott, Christopher; Kelham, Stephanie; Zhang, Liu; Grieve, Stacy; Lan, Tommy; Moradian, Hoora; Coll‐Ortega, Cristina; Gómez‐Ulloa, David (Transfusion medicine (Oxford, England), 2025)
This study aimed to assess the concordance and comparative accuracy of commercially available immunohematology (IH) tests for pretransfusion testing. Pretransfusion tests are intended to ensure donor blood is matched with a compatible recipient. Automated testing has become the mainstay since the commercialisation of IH analysers, because of their reduced risk of human error and increased efficiency. A systematic literature review (SLR) was performed to identify studies evaluating the concordance and sensitivity/specificity of IH tests for ABO/RhD typing, antibody screening, or antibody identification. Pairwise meta-analysis of concordance and sensitivity/specificity of IH tests was conducted when feasible. The SLR identified 48 publications, of which 30 were included for meta-analysis. ID/IH gel (Bio-Rad), DG gel (Grifols), MTS/BioVue gel (Ortho Clinical Diagnostics), and Capture R (Immucor/Werfen) all had almost 100% pooled concordance with each other in ABO/RhD typing and antibody screening. Antibody identification results varied across studies, and pooled concordance rates were lower: 97.53% for DG gel versus ID/IH gel, 85.26% for ID/IH gel vs. MTS/BioVue gel, 85.54% for DG gel versus MTS/BioVue gel, and 71.19% for Capture R versus MTS/BioVue gel. For antibody screening, ID/IH gel, DG gel, and MTS/BioVue gel had pooled sensitivities of 94.23%, 96.31%, and 97.27%, respectively, with a pooled specificity of ~100% for all three tests. All tests had good concordance in ABO/RhD typing and antibody screening, and lower pooled concordance rates for antibody identification. For antibody screening, 95% pooled sensitivity and ~100% specificity were estimated for DG gel, MTS/BioVue gel, and ID/IH gel.